Innovations For Active Arabic With the Kitab Al-Wajiz Fillughoti Wa Nahwi/ Inovasi Aktif Berbahasa Arab dengan Kitab Al-Wajiz Fillughoti wa Nahwi - Salamah, Umi; Supriyatno, Triyo (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
Language is a means of communication in conveying specific intentions and objectives. Arabic is the second language and language that Muslims must learn to understand the Qur'an, worship, and communicate. The aim of this research describes the active Arabic-speaking innovations with the book Al-Wajiz Fillughoti wa Nahwi and its impact on student language skills. This study used a qualitative approach with this type of case study. This research in Islamic dormitory Salafiyah A-Syarichin, Tajinan, Malang instrument is; Observations, interviews, and documentation made to teachers, and students. Data collection techniques, researchers do the interview, observation, and literature. This research data analysis technique; Data condensation (data condensation), 2) Presentation of data (display data); 3) Withdrawal of conclusions (Conclusions drawing). The results of this research are; The learning process is Arabic-speaking through stages: reading, memorizing, speaking. The impact of active learning speaks Arabic with the book Al-Wajiz Fillughoti wa Nahwi This is; students understand Arabic vocabulary, remember, and be able to do it in conversation, and ready to comprehend Nahwu, so that students are also able to read the book.